Spatial and temporal evaluation of the water quality index and trophic state index of the Curuçá River, Maranhão, Brazil - Souza, Neemias Muniz de; Araújo, Wanderson Pedro de Oliveira Carvalho; Rodrigues, Eduardo Henrique Costa; Silva, Maria Raimunda Chagas (Ciência e Natura, 2018)
This work aimed to evaluate the seasonal variations in the Water Quality Index and Trophic State Index in a given period. Physical and chemical analyses were performed according to APHA 2012 methods for water samples collected from the Curuçá River. The physicochemical parameters analyzed were temperature, pH, turbidity, total dissolved solids, conductivity, dissolved oxygen, biochemical demand, nitrite, nitrate, and total phosphorus; the results showed that there was significant variation between all the points collected in the dry periods and those established by the CONAMA 357/05. For the WQI, water was in the category of good to optimal, while according to the TSI, the aquatic environment of the Curuçá River was classified as ultraoligotrophic. Non-compliance with environmental norms for nutrients and bacteria was observed. Therefore, the presence of Escherichia coli with a value of <1000 CFU/100 mL was detected. The data were compared to the CONAMA 357/05, which showed that the data were inadequate for the maintenance of aquatic life. This analysis made it possible to verify the quality of this water, which is of environmental and socioeconomic interest to the population of the region where the springs will have to be preserved to improve the quality of the water.